2021
DOI: 10.1029/2021ef002277
|View full text |Cite
|
Sign up to set email alerts
|

Future Global Convective Environments in CMIP6 Models

Abstract: The response of climate extremes to increasing atmospheric CO 2 concentration has been studied in great depth in the last decade (Bindoff et al., 2013;Collins et al., 2013;Kunkel et al., 2013). The need to understand changes to these hazardous events motivated an IPCC report focused solely on the topic (Field et al., 2012, IPCC Special Report on Extremes, SREX). This report provided insight as to the limited confidence that the scientific community had in the expected changes of the extremes for a variety of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 67 publications
5
42
1
Order By: Relevance
“…For example, significant reductions are still seen in the southeastern US during DJF, and increases in the Rio de la Plata Basin during JJA. Lepore et al (2021) studied how convective severe weather activity changes in warmer climates for different seasons, based on analyzing environmental proxies of convection in the CMIP6 ensemble. They found that the metrics of frequency of severe weather activity increase globally as the global temperature increases, with higher latitudes showing larger relative changes.…”
Section: Global Picture Of Intense Convectionmentioning
confidence: 99%
“…For example, significant reductions are still seen in the southeastern US during DJF, and increases in the Rio de la Plata Basin during JJA. Lepore et al (2021) studied how convective severe weather activity changes in warmer climates for different seasons, based on analyzing environmental proxies of convection in the CMIP6 ensemble. They found that the metrics of frequency of severe weather activity increase globally as the global temperature increases, with higher latitudes showing larger relative changes.…”
Section: Global Picture Of Intense Convectionmentioning
confidence: 99%
“…Approximately half of tropopause‐overshooting convection in the United States reaches the stratospheric overworld (potential temperature >380 K; Cooney et al., 2018), suggesting these events can have significant, long‐lasting impacts on stratospheric composition since air extends deeper into the stratosphere and thus takes longer to slowly descend and return to the troposphere (Holton et al., 1995; Homeyer & Bowman, 2021). While trends in overshooting frequency in observations or those projected for future climates have not been explicitly studied, the frequency of such thunderstorms may increase with a warming climate given that the frequency of favorable severe thunderstorm environments is projected to increase (Del Genio et al., 2007; Lepore et al., 2021; Trapp et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…favorable severe thunderstorm environments is projected to increase (Del Genio et al, 2007;Lepore et al, 2021;Trapp et al, 2007).…”
mentioning
confidence: 99%
“…On a different note, numerous geophysical and anthropogenic events emit acoustic waves below the human hearing range of about 20 Hz, i. e., infrasound, including hurricanes and tornadoes. The rate of increase of severe storm environments becomes greater in the northern hemisphere due to temperatures rises [Lepore et al, 2021]. Tornado-producing storm systems emit infrasound up to 2 hours before tornado genesis.…”
Section: Meteorological Phenomenamentioning
confidence: 99%